1978
DOI: 10.1113/jphysiol.1978.sp012500
|View full text |Cite
|
Sign up to set email alerts
|

Chloride dependence of active sodium transport in frog skin: the role of intercellular spaces.

Abstract: SUMMARY1. In agreement with previous observations the replacement of Cl by a nonpenetrating anion in the solution bathing either the outside or both sides of the frog skin causes a fall in the short-circuit current.2. When Cl is replaced by a non-penetrating anion in the solution bathing the outside of the frog skin the I., is still a correct measure of the net Na transport.3. Under the same conditions both active and shunt paths seem to be affected since there is a decrease in In, Na influx, amiloride-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Although a very small fraction of Jw might be directly coupled to the inward flux of Na (Kirschner, Maxwell & Fleming, 1960;House, 1964;Ferreira & Hill, 1978;Lau, Parsons, Brady & Feeney, 1979), the flow of Na and water are essentially uncoupled in a tight epithelium such as toad skin. In particular, the large Jw values induced by hydrosmotic agents result from a selective increase in water permeability of the apical membrane and do not depend on a concomitant increase in Na transport, as seen in leaky epithelia.…”
Section: -9+10-2mentioning
confidence: 99%
“…Although a very small fraction of Jw might be directly coupled to the inward flux of Na (Kirschner, Maxwell & Fleming, 1960;House, 1964;Ferreira & Hill, 1978;Lau, Parsons, Brady & Feeney, 1979), the flow of Na and water are essentially uncoupled in a tight epithelium such as toad skin. In particular, the large Jw values induced by hydrosmotic agents result from a selective increase in water permeability of the apical membrane and do not depend on a concomitant increase in Na transport, as seen in leaky epithelia.…”
Section: -9+10-2mentioning
confidence: 99%
“…Their values for volume flow at normal conditions are the same as those measured by us for R. ridibunda (Ferreira & Hill, 1978) so we have used their values for volume flow at low pH. At pH 7 4, J, the fluid transport, is 0-69 1d.…”
Section: Discussionmentioning
confidence: 87%
“…Fischbarg & Whittembury (1978), who found that its rate was doubled by lowering the mucosal pH; Ferreira & Hill (1978) obtained similar rates of fluid transport for frog skin at normal pH. In order to calculate the osmolarity of the emergent fluid we decided to measure sodium fluxes at low and normal pH in open circuit as the water fluxes were measured also in open-circuit conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus for sodium and chloride it can be calculated from tracer experiments (Ussing & Windhager, 1964), but other ions may contribute to the shunt conductance. Or, the cellular sodium conductance can be eliminated by the sodium channel inhibitor, amiloride (Ferreira & Hill, 1978). However, the chloride conductance of the epithelium is drastically reduced by this procedure (see Kristensen, 1978).…”
Section: Discussionmentioning
confidence: 99%